People with disabilities: Identity, stigmatization, accommodation, and intersection with gender and aging effects on employment opportunities. In Bendl, R., Bleijenbergh, I., Henttonen, E., & Mills, A. J., The Oxford Handbook of Diversity in Organisation - Baldridge,David; Beatty,Joy; Konrad,Alison; Moore,Mark (2018)
Disability status continues to have a significant negative impact on employment outcomes, even in countries with nondiscrimination policies, and outcomes differ by gender and age. These subpar outcomes can be linked to both environmental and psychological factors. The design of jobs and workplaces often limits the ability of workers with disabilities to contribute to their fullest capacity. Stigmatization on the basis of disability status reduces employer willingness to hire workers with disabilities and make reasonable accommodations to allow them to perform effectively. Some research indicates that women, older workers and workers with disabilities tend to be labeled as unwilling or unable to perform in demanding paid work roles. Age intersects with disability resulting in inappropriate attribution of disability status as “normal aging.” Gender intersects with disability to result in lower labor force participation for women with disabilities compared to their male counterparts. Exclusion and stigmatization create barriers to the development of a positive self-identity as a person with a disability, but such identity development can be empowering, creating a sense of pride and providing a basis for advocacy. Considerably more research is needed to understand how the actions of organizations, leaders, and teams affect the employment outcomes of workers with disabilities and how impacts differ by gender and age. But based upon extant knowledge, there are many actions employers can take to improve outcomes for this group of workers.
Keywords: Management